Bioceramics and Scaffolds: A Winning Combination for Tissue Engineering - Baino, Francesco; Novajra, Giorgia; Vitale-Brovarone, Chiara (Frontiers in Bioengineering and Biotechnology, 2015)
In the last few decades we have assisted to a general increase of elder population worldwide with associated age-related pathologies. Therefore, there is the need for new biomaterials that can substitute damaged tissues, stimulate the body’s own regenerative mechanisms and promote tissue healing. Porous templates referred to as “scaffolds” are thought to be required for three-dimensional tissue growth. Bioceramics, a special set of fully, partially or non-crystalline ceramics (e.g. calcium phosphates, bioactive glasses and glass-ceramics) that are designed for the repair and reconstruction of diseased parts of the body, have high potential as scaffold materials. Traditionally, bioceramics have been used to fill and restore bone and dental defects (repair of hard tissues). More recently, this category of biomaterials has also revealed promising applications in the field of soft tissue engineering. Starting with an overview of the fundamental requirements for tissue engineering scaffolds, this article provides a detailed picture on recent developments of porous bioceramics and composites, including a summary of common fabrication technologies and a critical analysis of structure-property and structure-function relationships. Areas of future research are highlighted at the end of this review, with special attention to the development of multifunctional scaffolds exploiting therapeutic ion/drug release and emerging applications beyond hard tissue repair.